Analisis Kualitas Pelayanan Administrasi di Unit Pelaksana Teknis Puskesmas Sembayat Kecamatan Manyar Kabupaten Gresik - Nahda Amelia; Prasetyo Isbandono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Administrative services are the first step for the public to access health services, so their quality needs to be considered. Based on pre-research at the Sembayat Community Health Center, several obstacles were still found, such as waiting times for services under certain conditions, suboptimal staff communication, and waiting room layout that needs to be improved. This study aims to analyze the quality of administrative services at the Sembayat Community Health Center Technical Implementation Unit (UPT) in Manyar District, Gresik Regency. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the quality of administrative services has generally been running well. In the tangible dimension, staff appear neat and supported by adequate facilities, although the waiting room layout and seating capacity still need to be optimized. In the reliability dimension, staff are able to provide services carefully, utilize service aids properly, and work according to standard operating procedures. In the responsiveness dimension, staff are responsive in assisting patients, providing directions, and following up on complaints, although queue management during busy visits still needs attention. In the assurance dimension, services have provided time certainty, cost transparency, and maintained the confidentiality of patient data. In terms of empathy, staff demonstrated a friendly, caring, and non-discriminatory attitude. Therefore, improvements to the waiting room, queue management, and consistent staff communication are still needed to support optimal service.